(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
The research was based on an interest in extracurricular activities in history study at Senior High School. The Historical Community chosen as the object of research was due to the consideration of which this community the solely extracurricular based on historical learning that exists in Bandung and has not yet received attention among academics. The method used in this research is a descriptive study. The results of this study indicate that the background to the establishment of the Historical Community (KOMPAS) is the development of a history study group that is engaged in developing students’ historical insight and skills. After the Historical Community (KOMPAS) was officially established as an extracurricular, this group attempted to create interactive history learning programs that support history learning. The impact of the historical Community at the 22 Senior High School Bandung is to provide a variety of learning resources in developing history learning materials.